Perkembangan Tari Tampuruang Di Sanggar Sabirullah Matador Kanagarian Pasir Talang Timur Kabupaten Solok Selatan - Albadri Albadri; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2020)
The research aims to reveal, describe, and analyze the development of the Tampuruang Dance in Sabirullah Matador dance studio, KanagarianPasirTalangTimur, Solok Selatan Regency.This research is a qualitative research usinga descriptive analysis method. The object of this research is Tampuruang Dance in NagariPasirTalangTimur, Sungai PaguSubdistrict, SouthSolok Regency. The type of data was primary and secondary data. The main instrument was the research itself. The data collection techniques were conducted through literature study, observation, interviews, and documentation. The data collected were analyzed by using interpretation techniques so that the truth can be obtained.The results show that the Tampuruang Dance Tradition had developed into creativeTampuraung Dance.This development can be seen from the motion management, dancers, floor patterns, accompaniment music, make-up and clothing, as well as time and venue. In its motion, there is a development of 4 motives. Inthe floor pattern, there is development of 17 floor patterns. In costumes, the colors and accessories used are also developed.In the musical instrument, there aresomeadditions of musical instruments: Bansi, talempong, andjimbe. Thus, the process of Tampuruang Dance development in NagariPasirTalang is supported because there is a desire from the Sabirullah Matador studio to maintainTampuruang Dance by turning it into an attractiveTampuruang dance creationso that it can be used by the community. In addition, it can be a place for youths to learn maintaining cultural heritage so that it becomes a local village identity.